2014
DOI: 10.3389/fpsyg.2014.00865
|View full text |Cite
|
Sign up to set email alerts
|

Use of the adult attachment projective picture system in psychodynamic psychotherapy with a severely traumatized patient

Abstract: The following case study is presented to facilitate an understanding of how the attachment information evident from Adult Attachment Projective Picture System (AAP) assessment can be integrated into a psychodynamic perspective in making therapeutic recommendations that integrate an attachment perspective. The Adult Attachment Projective Picture System (AAP) is a valid representational measure of internal representations of attachment based on the analysis of a set of free response picture stimuli designed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…We observed that the clinical and control group did not differ on the amount of segregated systems in the attachment narratives per se. This is in line with the findings from other researchers (Buchheim et al, ; Buchheim & George, ), who argued for an in‐depth analysis of traumatic contents and defensive mechanisms to extend our understanding of the unresolved pattern in psychiatric patients and transfer its relevance into the psychotherapeutic practice (George & Buchheim, ). In this respect, our control group demonstrated more thoughtful self‐exploration and confidence in their attachment figures availability to remain organized, whereas the clinical group more often demonstrated attachment dysregulation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that the clinical and control group did not differ on the amount of segregated systems in the attachment narratives per se. This is in line with the findings from other researchers (Buchheim et al, ; Buchheim & George, ), who argued for an in‐depth analysis of traumatic contents and defensive mechanisms to extend our understanding of the unresolved pattern in psychiatric patients and transfer its relevance into the psychotherapeutic practice (George & Buchheim, ). In this respect, our control group demonstrated more thoughtful self‐exploration and confidence in their attachment figures availability to remain organized, whereas the clinical group more often demonstrated attachment dysregulation.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that the clinical and control group did not differ on the amount of segregated systems in the attachment narratives per se. This is in line with the findings from other researchers (Buchheim et al, 2008;Buchheim & George, 2001), who argued for an in-depth analysis of traumatic contents and defensive mechanisms to extend our understanding of the unresolved pattern in psychiatric patients and transfer its relevance into the psychotherapeutic practice (George & Buchheim, 2014).…”
Section: Attachment and Childhood Traumasupporting
confidence: 90%
“…In conclusion, our study demonstrated the important role of unresolved attachment for maladaptive personality functioning in adolescents with a history of childhood maltreatment. For clinical practice, our results suggest that assessing traumatic attachment-related material might help adolescents understand the impact of their childhood traumatic experiences on their current interpersonal functioning and affect regulation (Gander, Diamond, et al, 2018;George & Buchheim, 2014). Recently established intervention strategies helping adolescents to face traumatic aspects related to unresolved attachment (Gander, Diamond et al, 2018) might lead to more adaptive emotion-regulation strategies in young patients with PD, particularly in interpersonal relationships.…”
Section: Resultsmentioning
confidence: 84%
“…The therapist, far from being frightened by the patient's fear (see Main & Hesse, ), will build an alliance based on trust and sharing (Fassone et al ., ; Liotti & Gilbert, ; Prunetti, Bosio, Bateni, & Liotti, ). In this way, he will represent a secure base for patients that will make it possible to delve into the abuse experiences (George & Buchheim, ) and to bring to the light memories and feelings segregated from consciousness (West & George, ). This collaborative attitude may reactivate exploration and contrast the lack of agency and related impotence, humiliation, and subordination that have been experienced in the violent relationship, and so can create the interpersonal context functional to reach two different but related therapeutic goals: both facilitating the rebuilding of agency (through an activation of subject to explore concrete strategies for exiting from their unbearable interpersonal situations) and integrating attachment‐related segregated systems in their memories.…”
Section: Discussionmentioning
confidence: 99%
“…The use of AAP for exploring IPV West and George (1999) discussed regarding IPV in terms of attachment disorganization, as the more profound form of relational insecurity, but whereas numerous AAP studies have examined defensive processing in victims of traumatic experiences (Benoit, Bouthillier, Moss, Rousseau, & Brunet, 2009;Buchheim et al, 2008;George & Buchheim, 2014;Juen, Arnold, Meissner, Nolte, & Buchheim, 2013), a few studies have examined the unresolved/resolved status in maltreated adolescents, analysing exclusively the role of cognitive mediators (Joubert, Webster, & Hackett, 2012;Webster, Hackett, & Joubert, 2009). But, in our knowledge, no study has specifically examined attachment in women victims of IPV using the AAP.…”
Section: Insecure Attachment Status and Ipvmentioning
confidence: 99%